2008
DOI: 10.1529/biophysj.108.136473
|View full text |Cite
|
Sign up to set email alerts
|

Electrotonic Myofibroblast-to-Myocyte Coupling Increases Propensity to Reentrant Arrhythmias in Two-Dimensional Cardiac Monolayers

Abstract: In pathological conditions such as ischemic cardiomyopathy and heart failure, differentiation of fibroblasts into myofibroblasts may result in myocyte-fibroblast electrical coupling via gap junctions. We hypothesized that myofibroblast proliferation and increased heterocellular coupling significantly alter two-dimensional cardiac wave propagation and reentry dynamics. Co-cultures of myocytes and myofibroblasts from neonatal rat ventricles were optically mapped using a voltage-sensitive dye during pacing and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
227
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(246 citation statements)
references
References 34 publications
16
227
2
1
Order By: Relevance
“…In a coculture model, increased myofibroblast/myocyte area decreased conduction velocity and degenerated a spiral re-entry into multiple waves, like a VF. 24 Thus, increased myocardial fibrosis and disarray in HCM usually decreases excitation propagation, leading to a conduction delay or block, a substrate of re-entrant arrhythmias. SAECG can noninvasively evaluate a delayed potential as a substrate of ventricular arrhythmias in several diseases, although a previous study suggested that SAECG was not always useful for identifying HCM patients with VT or SCD.…”
Section: Promotion Of Conduction Abnormality and Vt/vf By Myocardial mentioning
confidence: 99%
“…In a coculture model, increased myofibroblast/myocyte area decreased conduction velocity and degenerated a spiral re-entry into multiple waves, like a VF. 24 Thus, increased myocardial fibrosis and disarray in HCM usually decreases excitation propagation, leading to a conduction delay or block, a substrate of re-entrant arrhythmias. SAECG can noninvasively evaluate a delayed potential as a substrate of ventricular arrhythmias in several diseases, although a previous study suggested that SAECG was not always useful for identifying HCM patients with VT or SCD.…”
Section: Promotion Of Conduction Abnormality and Vt/vf By Myocardial mentioning
confidence: 99%
“…In this way, the fibroblast proliferation changed the form of the re-entry. In addition, because of the presence of the fibroblasts, the CV slowed (Miragoli et al, 2006;Zlochiver et al, 2008), which contributed to stabilization of the spiral wave. This further illustrates that fibroblast proliferation aggravated the cardiac condition.…”
Section: Effects Of Fibroblast Proliferation At the Tissue Levelmentioning
confidence: 99%
“…Therefore, the functional roles of the fibroblasts in cardiac electrical and mechanical activities have attracted increasing interest, and have been explored in experimental studies (Miragoli et al, 2007;Zlochiver et al, 2008) and computational models (MacCannell et al, 2007;Tanaka et al, 2007;Jacquemet and Henriquez, 2008;Zlochiver et al, 2008;Sachse et al, 2009). Both experimental and computational studies (Miragoli et al, 2006;Jacquemet and Henriquez, 2008;Zlochiver et al, 2008) have illustrated that non-monotonic changes in conduction velocity (CV) are caused by increasing the fibroblast population. ten Tusscher and Panfilov (2007) showed that CV decreased from 0.7 to 0.3 m/s as the percentage of fibroblast proliferous cells rose from 0 to 40% in two-dimensional (2D) tissue.…”
Section: Introductionmentioning
confidence: 99%
“…By co-culturing neonatal cardiomyocytes and fibroblasts at different fibroblast infiltration ratios, Zlochiver et al reported that the electrical interaction between myocytes and fibroblasts determines rotor dynamics by altering the conduction velocity and wavefront complexity [16]. In vitro models also allowed the evaluation of the effects of mechanical stretch on the calcium dynamics and the mechanisms of initiation of AF in a model of HL-1 cells (i.e.…”
Section: Experimental Models With Persistent Atrial Fibrillationmentioning
confidence: 99%